2014
DOI: 10.4238/2014.march.24.1
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of common bean cultivars using multiplexed microsatellite markers

Abstract: ABSTRACT. Analysis of DNA polymorphisms allows for the genetic identification and precise discrimination of species with a narrow genetic base such as common bean. The primary objectives of the present study were to molecularly characterize commercial common bean varieties developed at various research institutions using microsatellite markers and to determine the degree of genetic diversity among the bean varieties analyzed. Fifty cultivars representing 12 grain classes and 64 genitors, i.e., accessions used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 25 publications
2
18
1
Order By: Relevance
“…There was variation of 2-4 alleles per locus, with the primers PvBR25 and ATA6 being the most informative (Table 4). Cardoso et al (2013Cardoso et al ( , 2014 found a mean number of alleles per locus greater than that seen in the present study. In 2013, the authors evaluated the genetic divergence of 172 common bean lines and cultivars making up five VCU trials conducted by the genetic breeding program of Embrapa Arroz e Feijão using 30 pairs of polymorphic primers.…”
Section: Resultscontrasting
confidence: 54%
“…There was variation of 2-4 alleles per locus, with the primers PvBR25 and ATA6 being the most informative (Table 4). Cardoso et al (2013Cardoso et al ( , 2014 found a mean number of alleles per locus greater than that seen in the present study. In 2013, the authors evaluated the genetic divergence of 172 common bean lines and cultivars making up five VCU trials conducted by the genetic breeding program of Embrapa Arroz e Feijão using 30 pairs of polymorphic primers.…”
Section: Resultscontrasting
confidence: 54%
“…The panel of 24 microsatellite loci used in this study is being routinely used at different stages of the common bean breeding program conducted by Embrapa and partners. In addition to the confirmation of controlled crosses and the detection of genetic identity of genotypes, other microsatellite marker applications include studies of genetic diversity among parents and elite lines, monitoring of allelic diversity and genetic representation of parents in breeding populations obtained by backcrosses and recurrent selection, aside from the control of genetic purity during the seed production process (Batista et al 2014, Cardoso et al 2014. It is worth mentioning that this molecular tool is available for immediate adoption and use by other common bean breeding programs in Brazil and worldwide.…”
Section: Resultsmentioning
confidence: 99%
“…However, this yield is low considering the crop's potential, which can reach 4.5 Mg/ha. This legume is an important source of protein for the Brazilian population, particularly for low-income groups (Cardoso et al, 2014;Pereira et al, 2014). Therefore, it is necessary to select highly productive genotypes that are adapted to the soil and climatic conditions of particular locations, which will increase the average national yield.…”
Section: Introductionmentioning
confidence: 99%